WRITERS FOR WRITERS: BOOKS WITH DEDICATION INSCRIPTIONS IN THE HOLDINGS OF THE WROBLEWSKI LIBRARY OF THE LITHUANIAN ACADEMY OF SCIENCES - NARBUTIENĖ, DAIVA (Knygotyra, 2015)
The aim of this article is to discuss dedication inscriptions by the authors in books from personal libraries of several Lithuanian writers as an aid for at least partial reconstruction of such libraries. The main source for this research is a card catalogue of books with dedications from the holdings of the Rare Book Department of the Wroblewski Library of the Lithuanian Academy of Sciences (hereafter WLLAS). The books with dedications listed in the catalogue have been examined de visu. Such a method is able to identify only part of the books previously owned by the writers in question. Three cases – the books dedicated by the authors to three writers – were selected for further analysis. These books, together with their former owners’ personal archives, came to the WLLAS Rare Book Department by the way of donation. The article presents an analysis of eleven books from the library of the poet, translator and children‘ s book writer Matas Grigonis (1889–1971). All the books carry gift inscriptions from their authors to the writer himself or his family. They were given to the library by the writer’s son, Matas Kastytis Grigonis, along with some archival documents, which supplemented the Matas Grigonis Archive Collection F202, already formed in the WLLAS Manuscript Department. Another case is a set of 47 autographed books from the private library of the poet Vladas Gurnevičius-Ramaškonis (1923–2002). They were given to WLLAS by the owner himself in 1992, together with his personal archive. In 1992–1993 the holdings of the Rare Book Department were enriched by books dedicated by the authors to emigrée writer Anatolijus Kairys (1914-08-28, St. Petersburg – 2008. U.S.A.) At the same time, in the WLLAS Manuscript Department, the Anatolijus Kairys personal archive collection (F337) was established, donated by the writer himself and later repeteadly supplemented. All three cases are connected by a common trait: authorial dedications, indicating book ownership. The dedications provide insights into socializing specifics of the book owners, a factor affecting certain aspects of book culture.